"Employability is not inimical to good learning" *: rearticulating school academic curricula to surface their employability value. Issue 1 (5th January 2021) - Daubney, Kate
Abstract : Purpose: This paper introduces a new approach to extracting the employability value of school/further education (FE) curriculums, using textual analysis to surface the transferable skills from UK curriculum documentation. The higher education extracted employability concept already established by the author is applied to help learners articulate the skills value of their knowledge-focused qualifications, closing the gap between the academic learning and the workplace. Proposals for additions to existing curriculum documentation would enable delivery of the Organisation for Economic Co-operation and Development's (OECD's) aspiration to embed skill development in school education. Design/methodology/approach: Manual textual analysis of United Kingdom A Level, General Certificate of Secondary Education (GCSE) and Scottish academic qualifications surfaced a database of transferable skills, which are categorised, and their interrelationships were analysed. Findings: Relatively few skills are explicitly articulated in curriculum documentation, revealing issues for learners recognising and articulating transferable skills. Extracted employability surfaces significant value from curriculum by identifying over 200 transferable skills, framed in the language employers recognise, thus closing the perceived "skills gap". Comparisons reveal significantly greater diversity of skills innate to subjects perceived as "less academic". Practical implications: Learners will find it easier to recognise a comprehensive language of transferable skills, aligned with what employers need, and fundamental to career decision-making through understanding the relationships between academic qualifications and work. Social implications: Learners who understand the wider value of their qualifications beyond knowledge focus, particularly in relation to transferable skills, are better able to be join, navigate and be agile in a challenging employment market. Originality/value: Higher education (HE) concepts of employability are not well-established or understood in schools. This new approach articulates it through transferable skills within existing academic curriculum.